Laminar flow and heat transfer in a smooth tube with a twisted-tape insert. - Du Plessis, Jean Prieur,1946- (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D) -- University of Stellenbosch, 1982.